Safety Indicator for Taxi Users In Urban Area - Wahab, Siti Norida; Anuar, Marhani Mohamed; Hong, Tong Wei; Tan, Yap Jor; Sham, Rohana (ExcelingTech, 2019)
Transportation service provided as social responsibility in many country including Malaysia should always be safe and perceived as safe by everyone. However, many studies had found that the increasing level of crime had cause the level of fear increase as well. Thus this had effected the ridership drop on almost all public transport usage especially taxi. Therefore it is the main intention of this paper to look at the different factors affecting the level of safety indication among taxi users in urban area. The paper provide an overview of the factors explaining on how different level of travel satisfaction through a quantitative research method where a personal administered survey was conducted among the taxi users who is living and commuting to the city center using taxi service. One of the significant findings shows that certain element such as driver attitude, age and technology indicate a significant roles as travel safety indicator. As this study only focus in urban area in Klang Valley, therefore the finding cannot be generalize to other area. Among the implication of the findings is that, future planner should take into consideration all factors that could possibly create a low signal of safety level among taxi users. This paper highlight the fear reduction model through a Malaysian empirical evidence which hold a high level of novelty where the application is suitable in Malaysian context urban travelers especially when reducing level of fear among taxi users is concern.